Polytriphenylamine sulfone compound and application thereof in detection of explosive TNT and drug budesonide
Through the preparation of D-A type polytrianiline sulfone compounds, the complex preparation steps and low quantum yield problems of TNT detection in water in the prior art are solved, and TNT detection with high sensitivity and low detection limits are achieved. The test of the drug budesonide is also well responsive.
Patent Information
- Application Number
- CN202411379222.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-07
AI Technical Summary
The existing triphenylamine polymers have problems such as complex preparation steps, low quantum yield, insufficient detection sensitivity and high detection limit in water TNT detection, and insufficient detection sensitivity to drug budesonide.
The D-A type polytriphenylsulfone compound was prepared by a one-step C-N coupling reaction method, and the reaction was carried out by 4,4'-difluorodiphenylsulfone, N,N'-diphenylbenzidine and potassium carbonate under a nitrogen atmosphere to obtain High fluorescence properties of polymers.
The low detection limit and high detection stability of TNT in water are achieved, with a detection limit of 94 nM, and has good anti-interference ability to TNT and is almost immune to pH, other nitro compounds, metal cations and anions. At the same time, the detection of the drug budesonide also showed high sensitivity.
Smart Images

Figure CN119390973A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental detection and drug detection, and specifically relates to a DA type polytriphenylamine sulfone compound and its application in detecting the content of explosive TNT in water and detecting drug budesonide suspension. Background Art
[0002] 2,4,6-Trinitrotoluene (TNT) is a high explosive widely used in military and industrial fields. However, TNT is biologically toxic, difficult to degrade, and can cause irreversible destructive effects on the environment, so it is particularly important to monitor TNT in the environment.
[0003] On the other hand, the drug budesonide suspension is mainly used for the treatment of non-glucocorticoid-dependent or dependent bronchial asthma and asthmatic chronic bronchitis, and can replace or reduce oral steroid treatment. When using budesonide, the dosage needs to be controlled (generally not more than 4 mg / day), so it is necessary to find a method for detecting the drug budesonide suspension.
[0004] In recent years, in the face of the requirements of pollution-free environment and high-quality drugs, the demand for environmental testing and drug testing has continued to increase. For example, the content of nitroaromatic pollutants such as TNT in water bodies, or the detection of the dosage of drug budesonide suspension is facing challenges. Although various instrument-based analytical techniques have developed rapidly, covering a variety of methods such as chromatography, mass spectrometry, gas chromatography-mass spectrometry, X-ray imaging, Raman spectroscopy, ion mobility spectrometry, electrochemical analysis, etc., the emergence of these technologies has greatly promoted the progress of detection technology. However, these devices are often bulky and difficult to carry, and it is difficult to meet the needs of real-time and on-site monitoring, especially in outdoor environmental monitoring occasions where data needs to be obtained quickly. This limitation not only reduces the efficiency of on-site detection, but also increases the feedback time. In contrast, fluorescence-based detection methods have been used in portable detection equipment as early as the last century due to their simple operation, low cost, high sensitivity and excellent selectivity, and have therefore been widely used.
[0005] As a classic organic semiconductor material, triphenylamine shows great potential in the construction of fluorescent probes due to its unique electron-rich properties, geometric configuration and chemical stability. However, the current triphenylamine-based fluorescent probe materials face many challenges, such as complex synthesis, low yield and difficulty in large-scale production.
[0006] Typically, the synthesis of triphenylamine polymers requires the introduction of reactive functional groups in advance, followed by polymerization reactions. This method inevitably involves more synthesis steps and higher costs. In addition, unmodified triphenylamine polymers exhibit low quantum yields in aqueous media, and usually require modification with aggregation-induced emission (AIE) groups such as tetraphenylethylene to enhance the luminescence efficiency of the aggregated state. This limitation seriously affects the application of triphenylamine polymers as fluorescent probes for TNT in water.
[0007] Therefore, there is an urgent need to provide a triphenylamine polymer that has a simple preparation method, high yield, low detection limit for TNT in water, high detection sensitivity for drug budesonide suspension, good anti-interference ability, and is almost unaffected by potential factors such as pH, other nitro compounds, metal cations and anions. Summary of the invention
[0008] The present invention aims to solve the above technical problems, thereby providing a DA type polytriphenylamine sulfone compound and its application in the detection of explosive TNT content in water and drug budesonide, so as to solve the problems of the existing triphenylamine polymers, such as complicated preparation steps, low quantum yield, insufficient detection sensitivity for TNT and budesonide, and high detection limit.
[0009] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0010] The present invention first provides an application of a DA-type polytriphenylamine sulfone compound in detecting the content of explosive TNT and the drug budesonide in water. The structural formula of the DA-type polytriphenylamine sulfone compound is shown in the following formula <Ⅰ>:
[0011]
[0012] Wherein, said n is a repeating unit;
[0013] The DA type polytriphenylamine sulfone compound is prepared by a one-step CN coupling reaction using 4,4'-difluorodiphenyl sulfone, N,N'-diphenylbenzidine and potassium carbonate under a nitrogen atmosphere.
[0014] The present invention uses diaromatic amine compounds and difluoroaromatic compounds as raw materials and successfully prepares a DA type triphenylamine polymer through a one-step CN coupling reaction. The structure and stability of the polymer are characterized by infrared, nuclear magnetic resonance, thermal analysis and other means, and its photophysical parameters such as ultraviolet absorption spectrum, fluorescence spectrum, fluorescence lifetime and quantum yield are tested. The DA type polytriphenylamine sulfone compound has strong luminescence performance in water It can be well used for the detection of trace TNT and the drug budesonide. The Stern-Volmer constant of the DA type polytriphenylamine sulfone compound for TNT is 2.98×10 5 M -1 , with a detection limit of 94nM. At the same time, its detection of TNT showed good anti-interference ability and was almost unaffected by potential factors such as pH, other nitro compounds, metal cations and anions.
[0015] In addition, the DA type polytriphenylamine sulfone compound prepared by the present invention not only responds to TNT, but also has a good response effect to budesonide suspension.
[0016] Furthermore, the Stern-Volmer constant of the DA type polytriphenylamine sulfone compound for TNT is 2.98×10 5 M -1 The detection limit of TNT in water is 94nM.
[0017] Furthermore, the pH value of water containing TNT is 1-12.
[0018] The second object of the present invention is to provide a DA-type polytriphenylamine sulfone compound for detecting TNT content and drug budesonide in water, wherein the structural formula of the DA-type polytriphenylamine sulfone compound is shown in the following formula <Ⅰ>:
[0019]
[0020] Wherein, the n is a repeating unit.
[0021] Furthermore, the thermal decomposition temperature of the DA type polytriphenylamine sulfone compound is 460°C, and the glass transition temperature is 231°C.
[0022] Furthermore, the average lifetime (<τ>avg) of the DA-type polytriphenylamine sulfone compound is 3.78ns, and the fluorescence quantum yield in water is is 0.27.
[0023] The third object of the present invention is to provide a method for preparing the DA-type polytriphenylamine sulfone compound for detecting the TNT content in water and the drug budesonide as described above, which is prepared in a one-step manner by CN coupling reaction using 4,4'-difluorodiphenyl sulfone, N,N'-diphenylbenzidine and potassium carbonate under a nitrogen atmosphere.
[0024] Furthermore, the molar ratio of the 4,4'-difluorodiphenyl sulfone to N,N'-diphenylbenzidine is 1:1 to 1:1.5.
[0025] Furthermore, the molar ratio of the 4,4'-difluorodiphenyl sulfone to potassium carbonate is 1:1.5 to 1:2.
[0026] Furthermore, the reaction temperature is 220-240° C., and the reaction time is 16-20 hours.
[0027] The beneficial effects of the present invention are as follows:
[0028] The DA type polytriphenylamine sulfone compound provided by the present invention has the advantages of low detection limit and good detection stability in the detection of TNT in water and the detection of the drug budesonide; while other triphenylamine polymers and several other DA type polytriphenylamine sulfone compounds have poorer detection effects on TNT than the compound of the present invention. In addition, the DA type polytriphenylamine sulfone compound of the present invention also has good responsiveness to budesonide. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 (a) Infrared spectrum of monomers (A: N,N'-diphenylbenzidine; B: N,N'-diphenyl-p-phenylenediamine; C: N,N'-di(2-naphthyl)-p-phenylenediamine; D: 4,4'-difluorodiphenyl sulfone; E: 4,4'-difluorobenzophenone); (b) Infrared spectrum of polymers.
[0030] Figure 2 This is the H NMR spectrum of the polymer.
[0031] Figure 3 TGA (a) and DSC (b) of the polymer.
[0032] Figure 4 (a) UV-visible absorption spectrum of polymer powder; (b) photograph of the polymer under sunlight.
[0033] Figure 5 (a) Fluorescence spectrum of polymer powder; (b) Photograph of polymer under UV light.
[0034] Figure 6 This is the transient fluorescence decay curve of the polymer powder.
[0035] Figure 7 UV-visible absorption spectra of PTPAS-1(a), PTPAK-1(b), PTPAS-2(c), PTPAK-2(d), PTPAS-3(e) and PTPAK-3(f) in different solvents. Figure 8 Fluorescence spectra of PTPAS-1 (a), PTPAK-1 (b), PTPAS-2 (c), PTPAK-2 (d), PTPAS-3 (e), and PTPAK-3 (f) in different solvents.
[0036] Fig. 9 Changes in fluorescence intensity and maximum emission wavelength of the polymers in different ratios of THF / H2O, (a) PTPAS-1; (b) PTPAS-2; (c) PTPAS-3; (d) PTPAK-1; (e) PTPAK-2; (f) PTPAK-3.
[0037] Fig.10 (a) Detection of TNT by PTPAS-1; (b) Stern-Volmer equation fitting curve of PTPAS-1 for TNT; (c) response time of PTPAS-1 solutions of different concentrations to TNT.
[0038] Fig.11 Detection of TNT by PTPAS-1 at different pH values.
[0039] Fig.12 Fluorescence spectra after adding different nitro compounds (a), metal ions (c) and anions (e) to the PTPAS-1 solution; changes in fluorescence intensity after adding different nitro compounds (b), metal ions (d) and anions (f) to the PTPAS-1 solution.
[0040] Fig.13 The average particle size and fluorescence intensity changes of PTPAS-1 aqueous solution within three weeks. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0042] Example 1
[0043] 1. Experimental instruments and raw materials
[0044] Table 1 Experimental drugs
[0045]
[0046] Table 2 Main experimental equipment
[0047]
[0048] 2. Preparation of polymers
[0049] Referring to the following reaction formula (I), six triphenylamine polymers were synthesized by CN coupling, including three polytriphenylamine sulfones (PTPAS-1, PTPAS-2 and PTPAS-3) and three polytriphenylamine ketones (PTPAK-1, PTPAK-2 and PTPAK-3). The specific preparation methods are as follows:
[0050]
[0051] Taking the preparation of PTPAS-1 as an example (the preparation methods of the other five polymers are similar, and the mass of the added raw materials is converted according to the molar amount), under a nitrogen atmosphere, 4,4'-difluorodiphenyl sulfone (2.54g, 10mmol), N,N'-diphenylbenzidine (3.36g, 10mmol) and anhydrous potassium carbonate (2.07g, 15mmol) were added to a three-necked bottle equipped with a stirrer, and then 10mL of cyclopentane sulfone and 5mL of chlorobenzene solution were added dropwise, and the reaction system was stirred to mix evenly, and the reaction was continued at 220°C for 16 hours. After the reaction was completed, the reaction solution was poured into anhydrous ethanol for precipitation, filtered and washed with distilled water several times, and the raw materials and oligomers were completely removed with anhydrous ethanol through a Soxhlet extractor, and vacuum dried for 5 hours to obtain 5.3g of light gray powdered polymer with a yield of 76%.
[0052] In the above preparation method, the molar ratio of the raw materials is between 1:1:1.5 and 1:1.5:2, the reaction temperature is between 220 and 240°C, and the reaction time is between 16 and 20 hours, and the above six polymers of the present invention can be obtained.
[0053] 3. Polymer Characterization and Performance Testing Methods
[0054] (1) Thermal stability
[0055] The DSC and TGA curves of the polymers were obtained by differential scanning calorimeter Netzsch DSC214 and thermal analyzer Mettler TGA2, respectively, in a nitrogen atmosphere at a heating rate of 10 K / min.
[0056] (2) Fluorescence properties in different solvents
[0057] 1 mg of polymer was added into glass bottles containing 20 mL of different solvents (cyclohexane (HEX), trichloromethane (TCM), ethyl acetate (EA), dichloromethane (DCM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethanol (EtOH), methanol (MeOH)). After complete dissolution, the polymer was excited with 365 nm ultraviolet light to test the fluorescence spectrum of the polymer in each solvent.
[0058] (3) Fluorescence quantum yield
[0059] Prepare a polymer solution with an absorbance of less than 0.05 at a UV wavelength of 360 nm, and use quinine sulfate solution ( The solvent is 0.05 mol / L H2SO4 aqueous solution) as a reference sample. After using a fluorescence spectrometer to test the fluorescence spectrum of the polymer in this solvent, the quantum yield is calculated using formula (1-1):
[0060]
[0061] In the formula, st and x represent the standard sample and the sample to be tested respectively. is the fluorescence quantum yield, F is the integrated area of the fluorescence peak, f is the absorption factor, and n is the refractive index of the solvent.
[0062] (4) Fluorescence lifetime
[0063] The fluorescence decay curve of the polymer was measured using a transient fluorescence spectrometer, and the fluorescence lifetimes τ1 and τ2 were obtained by second-order exponential fitting. Then, the average fluorescence lifetime (<τ> avg ).
[0064]
[0065] Where τ1 and τ2 are the fluorescence lifetimes obtained by second-order exponential fitting; B1 and B2 are the proportions of the fluorescence lifetime τ1 and τ2, respectively; <τ> avg represents the average fluorescence lifetime.
[0066] (5) Fluorescence properties of polymers in H2O / THF dual solvent system
[0067] Prepare 10 mL of H2O / THF solutions with volume ratios of 10:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:10, and add 100 μL of 1 g / L polymer solution to each solution. After oscillation and mixing, test the fluorescence spectra of the polymers at different water contents under 365 nm ultraviolet excitation.
[0068] (6) Detection of polymers on TNT and drug budesonide
[0069] Detection of TNT: Prepare 500mL of 0.01g / L polymer solution (H2O / THF=9:1, v / v), take 10mL and add it to a glass bottle, add 0μL, 2.5μL, 5μL, 7.5μL, 10μL, 17.5μL, 25μL, 37.5μL, 50μL, 75μL, 100μL of 1g / L TNT solution respectively, and test the fluorescence spectrum under 365nm ultraviolet light excitation after equilibrium. The Stern-Volmer constant (K) of the polymer for TNT is calculated by fitting equations (1-3) and (1-4). SV ) and limit of detection (LOD).
[0070]
[0071]
[0072] Where I0 is the initial fluorescence intensity of the fluorescent probe before adding TNT, I is the fluorescence intensity after the addition of TNT, [Q] is the concentration of TNT in the sample being tested, and K is sv is the Stern-Volmer constant, C L is the detection limit of the fluorescent probe, and S is 15 times the standard deviation of the blank sample.
[0073] Detection of budesonide suspension: Weigh a certain weight of polymer, transfer it to commercially available budesonide suspension, and test the fluorescence spectrum under 365nm ultraviolet light excitation.
[0074] (7) Response speed of polymer to TNT
[0075] Prepare 10 mL of a solution (H2O / THF=9:1, v / v) and add it to a glass bottle, then add 10 μL, 20 μL, 40 μL, 60 μL, 80 μL, and 100 μL of a 5 g / L polymer solution respectively, then measure 3.5 mL of each and add them to a cuvette, and also add 70 μL of a 2 mM TNT solution to the cuvette, and test under 365 nm ultraviolet light excitation to obtain a curve of the fluorescence intensity of the solution changing with time.
[0076] (8) Effect of pH on polymer properties
[0077] Prepare 10mL of solution with a pH value in the range of 1-12 and a volume ratio of H2O and THF of 9:1. Then, add 100μL of 1g / L polymer THF solution to each solution. After mixing evenly, add 3.5mL to the cuvette and test the fluorescence spectrum of the polymer solution under 365nm ultraviolet light excitation. Then, add 70μL of 2mM TNT solution to the previous cuvette. After the two fully respond, test the fluorescence spectrum of the polymer and TNT combined under 365nm ultraviolet light excitation.
[0078] (9) Polymer selectivity for TNT
[0079] First, prepare a 10 mM concentration of metal ion nitrate (Ag + 、Al 3+ , Ca 2+ 、Co 3+ , Cu 2+ , Fe 2+ , Fe 3+ Mg 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ ) and nitro compound (o-chloronitrobenzene (CNB), o-nitrophenol (NP), 1,3-dinitrobenzene (DNB), m-nitrobenzene (NT), nitrobenzene (NB), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (DNT), octogen (HMX), hexogen (RDX)) solution. Then, prepare 500mL of 0.01g / L polymer solution (THF / water = 1:9, v / v). Take 10mL of polymer solution and put it into a glass bottle, and then add 20μL of the prepared metal ion or nitro compound solution to each sample. After the fluorescence is stable, use 365nm ultraviolet light to excite and test its fluorescence spectrum.
[0080] (10) Stability of polymer solution
[0081] 200 mL of 0.01 g / L polymer solution (THF / H2O=1:9, v / v) was prepared, and 20 mL of the solution was taken out every three days for particle size analysis and fluorescence spectrum measurement for 21 days.
[0082] 4. Results and Discussion
[0083] 1. Structural characterization of polymers
[0084] The six prepared polymers all appeared as powdery solids, and their structures were further characterized by infrared and nuclear magnetic resonance. Figure 1 The infrared spectra of monomers and polymers are shown in Figure 2. Among the six polymers, the -1The disappearance of the NH stretching vibration peak belonging to the raw material at 1303 cm indicates that the NH bonds in the reactants have been fully reacted. -1 and 1142cm -1 The asymmetric stretching vibration peaks and symmetric stretching vibration peaks of the sulfone group appeared near 1650 cm-1 for PTPAK-1, PTPAK-2 and PTPAK-3. -1 The stretching vibration peak of the carbonyl group appears near the 6 polymers. Figure 2 As shown, due to the presence of a large number of benzene ring structures in their molecular structures, there is a certain degree of overlap in the hydrogen atom peak positions in the NMR spectrum within the range of 6.5-8ppm. However, at high chemical shifts, the hydrogen belonging to the imino group of the raw material has disappeared, which also confirms that the NH bond has completely reacted.
[0085] 2. Study on thermal stability of polymers
[0086] Figure 3 The TGA and DSC curves of the polymer. Figure 3 It can be seen that polytriphenylamine derivatives with different structures have different thermal stabilities. First, the thermal stability of PTPAS-3 and PTPAK-3 with naphthyl substituted side chains is much higher than that of the other four polytriphenylamine derivatives, with thermal decomposition temperatures of 493°C and 536°C, and residual carbon rates of 60.0% and 70.5%, respectively. This is because the introduction of larger naphthyl groups on the polymer side chains can inhibit the cleavage reaction of the main chain at high temperatures. Among the other four polymers, PTPAS-1 and PTPAS-2 with sulfone groups have moderate thermal decomposition temperatures of 460°C and 458°C, respectively, and PTPAK-1 and PTPAK-2 with carbonyl groups have thermal decomposition temperatures of 339°C and 343°C, respectively.
[0087] The DSC curves of the six polymers show that the polymers have undergone a significant glass transition. The polymers with sulfone groups have higher glass transition temperatures, with the glass transition temperatures of PTPAS-1, PTPAS-2 and PTPAS-3 being 231°C, 208°C and 219°C, respectively, while the glass transition temperatures of the polymers with carbonyl groups, PTPAK-1, PTPAK-2 and PTPAK-3, are 160°C, 162°C and 193°C, respectively. This is because the sulfone group has a stronger polarity, and the polymer chain with the sulfone group introduced is more rigid than that with the carbonyl group introduced, which ultimately leads to a higher glass transition temperature for the polymer with the sulfone group.
[0088] 3. Study on the photophysical properties of polymers
[0089] Figure 4The UV-visible absorption spectra of polymer powders. The six polymer powders have strong absorption in the UV range, which is mainly related to their π-π* transitions and n-π* transitions. Among them, the UV absorption of PTPAS-1 is mainly concentrated in 300-400nm, while the other five polymers show a strong absorption platform in the range of 200-400nm. In the visible light range, PTPAS-1 only has visible light absorption in the range of 390-450nm, and PTPAK-1 has visible light absorption in the range of 390-500nm.
[0090] like Figure 5 As shown in the figure, the fluorescence spectra of the six polymers show their different luminescence characteristics. The maximum emission wavelengths (λ em ) has a larger span, and the blue fluorescence emission (λ em =474 nm) to the red fluorescence emission of PTPAK-2 (λ em =610nm). Compared with the polymers with sulfone groups (PTPAS-1, PTPAS-2 and PTPAS-3), the polymers with carbonyl groups (PTPAK-1, PTPAK-2 and PTPAK-3) have a red-shifted maximum emission wavelength. Similarly, the maximum emission wavelength differences of polymers with different electron-donating groups (such as PTPAS-1, PTPAS-2 and PTPAS-3) also show a similar pattern. This is because the luminescent materials based on the ICT effect are affected by the electron-donating-withdrawing effect within the structure. Molecules with stronger electron-donating-withdrawing ability have a smaller HOMO-LUMO energy level difference, which leads to lower energy released when the electrons in the excited state return to the ground state, and a longer wavelength.
[0091] The length of the fluorescence lifetime is affected by the transition mode of the material from the excited state to the ground state. The transient fluorescence decay curves of six polymers were tested using a transient fluorescence spectrometer. The fluorescence lifetimes of the polymers (τ1 and τ2) were obtained by fitting the fluorescence lifetimes through secondary exponentials. The two fluorescence lifetimes represent different transition modes. The average fluorescence lifetime (<τ> avg ).like Figure 6 As shown in Table 3, PTPAS-1 has the longest fluorescence lifetime, with τ1 and τ2 of 1.53 ns and 5.6 ns, respectively. The two transition modes account for 74.78% and 25.22%, respectively. The average lifetime <τ> avg The calculated value is 3.78ns. The other five polymers have a higher percentage of fluorescence lifetime τ1, so the average fluorescence lifetime <τ> avg Much smaller than PTPAS-1. Generally, materials with longer fluorescence lifetimes have a higher proportion of radiative transitions and higher quantum yields.
[0092] Table 3 Quantum yield and fluorescence lifetime of polymer powders
[0093]
[0094] Note: In the table is the absolute quantum yield measured by the fluorescence spectrometer through an integrating sphere. “-” means that the quantum yield is less than 0.01 and it is difficult to measure the specific value through an integrating sphere. τ1 and τ2 are the fluorescence lifetimes of the second-order exponential fitting. avg is the average fluorescence lifetime.
[0095] The photophysical properties of polymers in different solvents were studied, such as Figure 7 The UV-visible absorption spectra of the six polymers in n-hexane (HEX), chloroform (TCM), ethyl acetate (EA), dichloromethane (DCM), tetrahydrofuran (THF), N,N-dimethylformamide (DMF), ethanol (EtOH) and methanol (MeOH) are shown. PTPAS-1 has only one absorption peak at 300-500nm, and its maximum absorption wavelength (λ abs ) is around 340nm. This absorption band is mainly caused by the π-π* transition of the benzene ring in the polymer. The other five polymers all have two absorption peaks. Their absorption bands in the short-wave direction are attributed to the π-π* transition of the benzene ring, while the absorption band in the long-wave direction is the ICT absorption band. Although PTPAS-2 and PTPAS-3 also have two absorption peaks, their ICT absorption bands and π-π* transition absorption bands overlap to varying degrees, and both appear around 360nm. In the UV-visible absorption spectra of polymers with carbonyl groups (PTPAK-1, PTPAK-2 and PTPAK-3), the ICT band appears around 390nm, and is more significantly separated from the π-π* transition absorption band. This shows that the lack of an obvious ICT absorption band in PTPAS-1 may be due to the overlap of the π-π* transition absorption band and the ICT absorption band. In addition, the maximum absorption wavelengths of the six polymers are affected by the polarity of the solvent. Taking PTPAS-2 as an example, its two absorption bands both have a red-shifted maximum absorption wavelength when the solvent polarity increases. The reason may be that the high dipole moment of the polar solvent can stabilize the excited state of the polymer, resulting in a decrease in the energy from its ground state to the excited state.
[0096] Figure 8The fluorescence spectra of six polymers in solvents of different polarities. The six polymers show significant differences in maximum emission wavelengths in solvents of different polarities, which is a characteristic of luminescent materials based on the ICT effect. Taking PTPAS-1 as an example, its maximum emission wavelength is 446nm in low-polarity solvents (HEX), while in high-polarity solvents (DMF), the maximum emission wavelength is 556nm, and there is a 90nm emission wavelength shift between the two. Only PTPAK-1, which has a different electron-withdrawing structure, shows a stronger solvent color change effect, with a maximum emission wavelength of 438nm in HEX and 586nm in DCM, and there is a 138nm emission wavelength shift between the two. This is due to the presence of a donor-acceptor structure in the polymer structure, which can achieve charge transfer (CT) from electron donors to electron acceptors in the excited state. The other four polymers also show similar trends, and the maximum emission wavelength is affected by the polarity of the solvent, and when the electron-donating structure is the same, the maximum absorption wavelength of polymers such as polytriphenylamine is more affected by the solvent.
[0097] The quantum yields in different solvents (Table 4) show that the quantum yields of the two polymers in high-polarity solvents are significantly lower than those in medium- and low-polarity solvents. This is due to the stronger solute-solvent interaction in high-polarity solvents. The dissipation of excited state energy in a non-radiative transition manner will significantly weaken the polymer fluorescence.
[0098] Table 4 Photophysical properties of PTPAS-1 and PTPAK-1 in different solvents
[0099]
[0100]
[0101] The fluorescence properties of the polymer in the THF / H2O dual solvent system are as follows: Fig. 9 As shown in the figure, the fluorescence of the six polymers all showed a decreasing trend at low water content. This is because when the water content is low, the fluorescence of the polymer is mainly affected by the polarity of the solvent. Take the test results of PTPAS-1 as an example ( Fig. 9In a), when the water content in tetrahydrofuran is continuously increased (0%-50%), due to the continuous increase in solvent polarity, the conformational changes and solute-solvent interactions of the ICT-based luminescent polymer in the excited state are strengthened, resulting in a continuous weakening of fluorescence and a significant change in the emission wavelength. When the water content is further increased (50%-70%), due to the continuous aggregation of particles in the solution, the luminescence mechanism gradually changes from liquid luminescence to solid nanoparticle luminescence. Since the distorted spatial structure of the polymer has a certain inhibitory effect on the accumulation of fluorophores in the aggregated state, a small increase in solution fluorescence is observed at this stage. When the water content is higher (70%-99%), due to the increased aggregation of the polymer in the solution, its fluorescence intensity will be weakened to a certain extent. In addition, PTPAK-2 ( Fig. 9 Figure (e) shows a phenomenon different from the other five polymers. With the increase of water content, the fluorescence intensity of PTPAK-2 shows a trend of first increasing and then decreasing. The reason for the fluorescence enhancement phenomenon in the water content range of 0%-20% may be that the change in the solvent mixing ratio causes other interactions, while the fluorescence quenching phenomenon in the range of 20%-99% is a typical aggregation-induced quenching (ACQ) phenomenon, which is caused by its geometric structure.
[0102] Table 5 Fluorescence quantum yields of six polymers in tetrahydrofuran and water
[0103]
[0104] Table 5 shows the fluorescence quantum yield data of the polymer in tetrahydrofuran and water. It can be seen that PTPAS-1 has excellent fluorescence properties. Its fluorescence quantum yield in tetrahydrofuran and water is 0.58 and 0.27, and can maintain 47% of the quantum yield in the solution state in the aggregated state. This is because the biphenyl structure in the PTPAS-1 molecule can extend the molecular chain, and at the same time, the tetrahedral configuration of the sulfone group can make the polymer structure more distorted. The combined effect of the two structures enables PTPAS-1 to maintain a higher fluorescence intensity in the aggregated state. The three polytriphenylamine ketones (PTPAK-1, PTPAK-2 and PTPAK-3) have two benzene rings of the benzophenone structure in the molecule that are almost on the same plane, which will cause them to accumulate intermolecularly in the aggregated state, resulting in fluorescence quenching, resulting in a significantly lower quantum yield in water than the same type of polytriphenylamine sulfone polymers; PTPAS-2 and PTPAS-3 do not have a biphenyl structure, and their ability to inhibit intermolecular accumulation is weaker than PTPAS-1. PTPAS-2 and PTPAS-3 can maintain 40% and 31% of the quantum yield in tetrahydrofuran in water.
[0105] 4. Detection of TNT by polymer
[0106] The limit of detection (LOD) is an important indicator for evaluating the performance of fluorescent probes. PTPAS-1 has good fluorescence properties in water and can be used to detect trace amounts of TNT in water. Fig.10 In a, the fluorescence intensity of the polymer solution gradually weakened with increasing TNT concentration in the solution. When the TNT concentration was 1.1 μM, PTPAS-1 quenched 30% of the initial fluorescence intensity; when the TNT concentration reached 11 μM, PTPAS-1 achieved 80% fluorescence intensity quenching. The curve was fitted by the Stern-Volmer equation ( Fig.10 As can be seen in b), when the TNT concentration is lower than 11 μM, the ratio of the initial fluorescence intensity to the fluorescence intensity after quenching equilibrium (I0 / I) and the TNT concentration (c TNT ) showed a good linear relationship. When the TNT concentration was higher than 11 μM, I0 / I and c TNT The relationship gradually deviates from linearity, which is because the Stern-Volmer equation is not applicable when the concentration of the test substance is too high. The test results show that the Stern-Volmer constant (K SV )2.98×10 5 M -1 The detection limit (LOD) was 94 nM, which means that PTPAS-1 has excellent fluorescence response characteristics to TNT (Table 6). The response time to TNT under different polymer concentration conditions is as follows Fig.10 As shown in c, for the same concentration of TNT, when the polymer concentration is higher than 80 μM, more than 95% fluorescence quenching can be achieved within 30 s, while when the concentration is lower than 80 μM, the polymer solution needs about 120 s to achieve a similar quenching effect.
[0107] Table 6 Performance comparison of PTPAS and reported TNT fluorescent probes
[0108]
[0109] Note: The references in Table 6 are as follows:
[0110] [1]Xu YW,Zhong C,Zhang BY,et al.Facile preparation oftetraphenylethylene-based porous polymer with dual role of adsorption and detection for trinitrotoluene[J].Polymer,2023,288:126454.
[0111] [2]Mukherjee A,Bhattacharya S,Chakravarty M.An unprecedentedpyridine-based dinuclear mixed-valent ReI / VII oxo-bridged complex:asolvatochromic and AIE-active probe for nanomolar detection of picric acidand trinitrotoluene[J].Dalton Transactions,2021,50(26):9144-9157.
[0112] [3]Liao Y,Hu L,Huang J,et al.A facile and novel AIE vesicle asnanoprobe for simple and rapid detection of TNT in water[J].SpectrochimicaActa Part A:Molecular and Biomolecular Spectroscopy,2024,307:123617.
[0113] [4]Liao Y,Hu L,Huang J,et al.A facile and novel AIE vesicle asnanoprobe for simple and rapid detection of TNT in water[J].SpectrochimicaActa Part A:Molecular and Biomolecular Spectroscopy,2024,307:123617.
[0114] [5]Dong W,Ma Z,Chen P,et al.Carbazole and tetraphenylethylene basedAIE-active conjugated polymer for highly sensitive TNT detection[J].MaterialsLetters,2019,236:480-482.
[0115] [6] Komikawa T, Tanaka M, Tamang A, et al. Peptide-functionalized quantumdots for rapid label-free sensing of 2,4,6-trinitrotoluene[J]. BioconjugateChemistry, 2020, 31(5): 1400-1407.
[0116] [7] SK.Pyrene substituted amphiphilic ROMP polymers asnano-sized fluorescence sensors for detection ofTNT in water[J].Polymer,2019,183:121868.
[0117] [8]Doan BK, Tran TVT, Nguyen TH, et al. One-pot synthesis of star-shapedconjugated oligomers based on 3-hexylthiophene, pyrene and triphenylamine asTNT chemosensors[J]. Journal of Photochemistry and Photobiology A: Chemistry, 2020, 394: 112496.
[0118] 5. Effect of pH on polymer properties
[0119] Generally, acidity and alkalinity have a significant effect on the fluorescence properties of polymers. The luminescence and detection properties of PTPAS-1 are affected by acidity and alkalinity. Fig.11As shown in the figure, PTPAS-1 exhibits very similar fluorescence emission characteristics in the pH range of 1-12. The fluorescence emission of PTPAS-1 is less affected by acidity and alkalinity, mainly because the triphenylamine group and sulfone group in PTPAS-1 have good stability and are difficult to be protonated or deprotonated. At the same time, after adding TNT solution, PTPAS-1 can show fluorescence quenching in the pH range of 1-12. It is worth noting that at pH = 12, the quenching degree of PTPAS-1 after adding TNT solution is slightly lower than that at other pH values, which may be due to the formation of J-polymers between TNT molecules under strong alkaline conditions. The formation of this dimer may increase the steric hindrance of the interaction between the polymer and it, and at the same time, the actual TNT concentration in the solution will also decrease with the formation of the dimer.
[0120] 6. Study on the selectivity of polymers for TNT
[0121] like Fig.12 As shown, different nitro compounds (CNB, DNB, DNT, HMX, NB, NP, NT, RDX), metal ions (Ag + 、Al 3+ , Ca 2+ 、Co 3+ , Cu 2+ , Fe 2+ , Fe 3+ Mg 2+ , Mn 2+ 、Ni 2+ 、Zn 2+ ) and anions (F - , Cl - Br - ,I - , SO4 2- 、SO3 2- 、CO3 2- PO4 3- 、HPO4 2- ,AcO - 、NO3 - ) and other potential interferents to investigate the selectivity of the material for TNT. The fluorescence of PTPAS-1 is less affected by common nitro compounds, metal ions and anions, but shows a significant quenching response to TNT. It can be seen that the insensitivity of PTPAS-1 to common interferents indicates that it has a wide range of application potential.
[0122] 7. Study on the stability of polymer solution
[0123] By monitoring the changes in the particle size and fluorescence characteristics of the nanoparticles in the polymer solution over time, the stability and shelf life of the tested polymer solution can be evaluated. The change in particle size can reflect the aggregation of polymer particles in the solution, while the change in fluorescence characteristics can provide feedback on the stability of the polymer molecular structure. The stability of the polymer solution was tested, and the average particle size and fluorescence intensity changes of the PTPAS-1 aqueous solution within three weeks were as follows: Fig.13 When the polymer aqueous solution was placed for 21 days, there was no obvious coagulation of the polymer solution, and its fluorescence characteristics and particle diameter did not change much, which shows that the polymer solution has a long shelf life.
[0124] 8. Conclusion
[0125] Six DA-type triphenylamine polymers were successfully synthesized using simple raw materials through CN coupling reaction, namely three polytriphenylamine sulfones (PTPAS-1, PTPAS-2, PTPAS-3) and three polytriphenylamine ketones (PTPAK-1, PTPAK-2, PTPAK-3). The six polymers were screened for their detection effects on TNT in water and their responsiveness to budesonide.
[0126] The results showed that the luminescence in water was stronger The DA-type triphenylamine polymer PTPAS-1 is more suitable for the detection of trace TNT in water and the detection of drug budesonide suspension. Its Stern-Volmer constant (K SV ) is 2.98×10 5 M -1 The detection limit (LOD) was 94nM and the fastest response time was 30s. It also had a fluorescence quenching response to the drug budesonide suspension. The detection effects of the other five DA-type triphenylamine polymers on TNT in water were not as good as PTPAS-1; in addition, the responsiveness of PTPAS-1 to budesonide suspension also showed that it can be well used for the detection of drug budesonide.
Claims
1. An application of a DA type polytriphenylamine sulfone compound in the detection of explosive TNT content and drug budesonide in water, characterized in that: The structural formula of the DA type polytriphenylamine sulfone compound is shown in the following formula <Ⅰ>: Wherein, said n is a repeating unit; The DA type polytriphenylamine sulfone compound is prepared by a one-step CN coupling reaction using 4,4'-difluorodiphenyl sulfone, N,N'-diphenylbenzidine and potassium carbonate under a nitrogen atmosphere.
2. The use according to claim 1, characterized in that: The Stern-Volmer constant of the DA type polytriphenylamine sulfone compound for TNT is 2.98×10 5 M -1 The detection limit of TNT in water is 94nM.
3. The use according to claim 1 or 2, characterized in that: The DA type polytriphenylamine sulfone compound has good anti-interference ability for the detection of TNT and is not affected by potential factors such as pH, other nitro compounds, metal cations and anions.
4. The use according to claim 1 or 2, characterized in that: The DA type polytriphenylamine sulfone compound has a fluorescence quenching response to budesonide.
5. The use according to claim 1 or 2, characterized in that: The pH of water containing TNT is 1-12.
6. A DA-type polytriphenylamine sulfone compound for detecting the explosive TNT content and the drug budesonide in water, characterized in that: The structural formula of the DA type polytriphenylamine sulfone compound is shown in the following formula <Ⅰ>: Wherein, the n is a repeating unit.
7. The DA type polytriphenylamine sulfone compound for detecting the explosive TNT content and the drug budesonide in water according to claim 6, characterized in that: The thermal decomposition temperature of the DA type polytriphenylamine sulfone compound is 460°C, and the glass transition temperature is 231°C; preferably, the average lifetime <τ>avg of the DA type polytriphenylamine sulfone compound is 3.78ns, and the fluorescence quantum yield in water is is 0.
27.
8. The method for preparing the DA type polytriphenylamine sulfone compound for detecting the explosive TNT content and the drug budesonide in water according to claim 6 or 7, characterized in that: It is prepared in a nitrogen atmosphere by a one-step CN coupling reaction using 4,4'-difluorodiphenyl sulfone, N,N'-diphenylbenzidine and potassium carbonate.
9. The preparation method according to claim 8, characterized in that: The molar ratio of the 4,4'-difluorodiphenyl sulfone, N,N'-diphenylbenzidine and potassium carbonate is 1:1:1.5 to 1:1.5:
2.
10. The preparation method according to claim 8, characterized in that: The reaction temperature is 220-240° C., and the reaction time is 16-20 hours.